Diaphragm, preparation method thereof and battery
By setting spirocyclic phosphate bisphenol-S as the flame retardant layer material on the base film surface of the lithium-ion battery separator, the problems of low collapse temperature and flammability of the separator are solved, and the high thermal stability and flame retardant performance of the separator are achieved, and the safety performance of the battery is improved.
Patent Information
- Application Number
- CN202411845268.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-04-22
AI Technical Summary
The collapse temperature of the existing lithium-ion battery separator is low and contains flammable organic matter, which leads to no flame retardant effect when the battery heat accumulates, and even aids ignition, endangers the personal safety of users.
A flame retardant layer is provided on the surface of the base film. The flame retardant layer material includes spirocyclic phosphate bisphenol-S. Through the synergistic effect of the P and S elements of the spirocyclic phosphate bisphenol-S, the thermal stability and flame retardant performance of the flame retardant layer are improved.
Effectively improve the flame retardant performance and thermal stability of the diaphragm, prevent the battery from burning under high temperature conditions, and improve the battery safety performance.
Smart Images

Figure CN119864598A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of battery technology, and in particular to a diaphragm and a preparation method thereof, and a battery. Background Art
[0002] Lithium-ion batteries have the advantages of high energy density, long cycle life, fast charging rate, and wide operating temperature range. They are widely used in new energy vehicles, power storage, and electronic products. The diaphragm plays the role of electronic insulation and ion transmission in the battery. However, the diaphragm provided in the related art (such as polyolefin porous membranes such as polyethylene and polypropylene, or composite diaphragms formed by stacking, agglomeration, and winding) has a low collapse temperature (the diaphragm collapse temperature refers to the temperature at which the diaphragm material used in electrochemical devices such as batteries loses its physical integrity and functionality at a specific temperature, resulting in it being unable to effectively separate the positive and negative electrode materials), and the organic matter contained in it is flammable. When the heat of the battery accumulates, the diaphragm has no flame retardant effect and may even help combustion, endangering the personal safety of users. Summary of the invention
[0003] The embodiments of the present invention provide a diaphragm and a preparation method thereof, and a battery, which can improve the technical problem of poor flame retardancy of the diaphragm.
[0004] In a first aspect, an embodiment of the present invention provides a diaphragm, comprising a base film and a flame retardant layer disposed on the surface of the base film, wherein the material of the flame retardant layer comprises spirocyclic phosphate bisphenol-S, and the structural formula of the spirocyclic phosphate bisphenol-S is
[0005] Where n is 500-2500.
[0006] In one embodiment, the thickness of the flame retardant layer is 3 μm to 8 μm; and / or
[0007] The thickness of the separator is 6 μm to 18 μm; and / or
[0008] The air permeability of the diaphragm is ≤1000sec / 100mL; and / or
[0009] The contact angle of the separator to the electrolyte is ≤ 60°; and / or
[0010] The breakdown strength of the diaphragm is ≥3.2N.
[0011] In one embodiment, the material of the base film includes one or more of polyethylene, polypropylene and cellulose.
[0012] In one embodiment, the material of the flame retardant layer further includes a binder.
[0013] In one embodiment, the binder includes one or more of polyvinylidene fluoride and carboxymethyl cellulose; and / or
[0014] The mass ratio of spirocyclic phosphate bisphenol-S to the binder is (3-10):1.
[0015] In a second aspect, an embodiment of the present invention provides a method for preparing a diaphragm, comprising the following steps:
[0016] Providing a flame retardant slurry, wherein the flame retardant slurry comprises spirocyclic phosphate bisphenol-S and a first solvent;
[0017] Providing a base film, subjecting the flame retardant slurry to film-forming treatment to obtain a wet film layer, and performing a first drying on the wet film layer to obtain a diaphragm;
[0018] Wherein, the structural formula of spirocyclic phosphate bisphenol-S is
[0019] Where n is 500-2500.
[0020] In one embodiment, the flame retardant slurry further includes a binder, and the preparation process of the flame retardant slurry includes:
[0021] Spirocyclic phosphate bisphenol-S, a binder and a first solvent are provided, and the spirocyclic phosphate bisphenol-S and the binder are dispersed in the first solvent to obtain a flame retardant slurry.
[0022] In one embodiment, the mass ratio of spirocyclic phosphate bisphenol-S, the binder and the first solvent is (3-10):1:(5-20).
[0023] In one embodiment, the first drying temperature is 85° C.-100° C., and the first drying time is 20 min-180 min.
[0024] In one embodiment, the preparation method of spirocyclic phosphate bisphenol-S comprises the following steps:
[0025] Providing pentaerythritol, phosphorus oxychloride, a catalyst and a second solvent, mixing the pentaerythritol, phosphorus oxychloride, the catalyst and the second solvent, performing a first heating reaction, cooling and filtering after the reaction, and then performing a second drying on the solid product obtained by filtering to obtain a spirocyclic phosphate dichloride;
[0026] Bisphenol-S, triethylamine and a second solvent are provided, spirocyclic phosphate diacyl chloride, bisphenol-S and the second solvent are mixed, triethylamine is added and a second heating reaction is carried out, the temperature is lowered after the reaction and the product is filtered, and a solid product obtained by the filtration is dried for a third time to obtain spirocyclic phosphate bisphenol-S.
[0027] In one embodiment, the mass ratio of pentaerythritol to phosphorus oxychloride is 1:(1-9); and / or
[0028] The mass ratio of spirocyclic phosphate diacyl chloride to bisphenol-S is (0.9-1.1):1; and / or
[0029] The reaction temperature of the first heating reaction is 70° C.-90° C., and the reaction time of the first heating reaction is 4 h-12 h; and / or
[0030] The reaction condition of the second heating reaction is heating to 70° C.-90° C., and the reaction time of the second heating reaction is 6 h-10 h.
[0031] In a third aspect, an embodiment of the present invention provides a battery, comprising the above-mentioned diaphragm or a diaphragm produced by the above-mentioned diaphragm production method.
[0032] Beneficial effects of the embodiments of the present invention:
[0033] In an embodiment of the present invention, a flame retardant layer is arranged on the surface of the base film, and the flame retardant layer material includes spirocyclic phosphate bisphenol-S. The P and S elements contained in the spirocyclic phosphate bisphenol-S act synergistically, so that the flame retardant layer has good thermal stability and flame retardancy, and the spirocyclic phosphate bisphenol-S has a high degree of polymerization, which can further improve the thermal stability and flame retardancy of the flame retardant layer, thereby effectively improving the flame retardant properties and thermal stability of the diaphragm. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] In order to more clearly illustrate the technical solutions in the embodiments of the present application, the drawings required for use in the description of the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0035] Figure 1 is the structural formula of spirocyclic phosphate bisphenol-S provided in the present application;
[0036] Figure 2 is the infrared spectrum of the spirocyclic phosphate bisphenol-S provided in Example 1 of the present application;
[0037] Figure 3 1 is a graph showing the shrinkage test results of the diaphragms provided in Example 9 and Comparative Example 1 of the present application;
[0038] Figure 4 This is a graph showing the flammability test results of the diaphragms provided in Example 9 and Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0039] The technical solutions in the embodiments of the present application will be clearly and completely described below in conjunction with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by those skilled in the art without making creative work belong to the scope of protection of the present application. In addition, it should be understood that the specific implementation methods described herein are only used to illustrate and explain the present application, and are not used to limit the present application.
[0040] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those generally understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.
[0041] In this application, unless otherwise stated, directional words such as "upper" and "lower" generally refer to the upper and lower parts of the device in actual use or working state, specifically the drawing direction in the accompanying drawings; while "inner" and "outer" refer to the outline of the device. In addition, in the description of this application, the term "including" means "including but not limited to". The terms first, second, third, etc. are used only as labels and do not impose numerical requirements or establish an order.
[0042] In this application, "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural.
[0043] In the present application, "at least one" means one or more, and "plurality" means two or more. "One or more", "at least one of the following" or similar expressions refer to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b, or c", or "at least one of a, b, and c" can all mean: a, b, c, ab (i.e., a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0044] The technical solution of this application is as follows:
[0045] In a first aspect, an embodiment of the present application provides a diaphragm, comprising a base film and a flame retardant layer disposed on the surface of the base film, wherein the material of the flame retardant layer comprises spirocyclic phosphate bisphenol-S, and the structural formula of the spirocyclic phosphate bisphenol-S is Where n is 500-2500.
[0046] In the present application, spirocyclic phosphate bisphenol-S has a high degree of polymerization and a long-chain structure, which makes it difficult to decompose when heated, and can maintain the integrity of the material even under an open flame, thereby having better flame retardant properties and thermal stability; at the same time, the high degree of polymerization makes it easier to form a dense carbon layer after heating, and the carbon layer is a good thermal insulator that can prevent heat from being transferred to the base film. At the same time, the carbon layer can also isolate oxygen, slowing down or preventing the combustion process; the high degree of polymerization spirocyclic phosphate bisphenol-S has low volatility, and releases less combustible gas during the combustion process, which helps to reduce the combustion rate and flame propagation. And spirocyclic phosphate bisphenol-S has better flame retardant properties than inorganic flame retardants, and has little effect on the mechanical properties of the diaphragm, and has less harm to the human body and the environment than halogen flame retardants, and spirocyclic phosphate bisphenol-S has good resistance to solvent dissolution, thereby effectively improving the safety performance of the battery.
[0047] It can be understood that the flame retardant layer can be provided on one side or both sides of the base film, and the flame retardant layer can completely cover the surface of the base film or partially cover the surface of the base film.
[0048] In some embodiments, the thickness of the flame retardant layer is 3 μm to 8 μm, for example, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, etc. In this way, the flame retardant layer can be effectively flame retardant, while the thickness of the diaphragm is controlled to control the energy density of the battery and save costs. The thicker the flame retardant layer, the better the flame retardant effect and the lower the shrinkage rate at high temperature.
[0049] In some embodiments, the material of the base film includes one or more of polyethylene, polypropylene and cellulose. In this way, the compatibility of the flame retardant layer and the base film can be improved.
[0050] In some embodiments, the material of the flame retardant layer further includes a binder, so that the spirocyclic phosphate ester bisphenol-S can be better compounded with the base film.
[0051] In some embodiments, the binder includes one or more of polyvinylidene fluoride and carboxymethyl cellulose.
[0052] In some embodiments, the mass ratio of spirocyclic phosphate bisphenol-S to the binder is (3-10):1, for example, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, etc. In this way, the flame retardant coating is not easy to fall off and has good flame retardant properties.
[0053] In some embodiments, the thickness of the diaphragm is 6 μm to 18 μm, for example, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 17 μm, 18 μm, etc. In this way, the battery can have better safety performance and higher energy density. If the thickness of the diaphragm is too thin, the safety performance of the battery will be reduced, and if the diaphragm is too thick, the energy density of the battery will be reduced.
[0054] In some embodiments, the air permeability of the diaphragm is ≤1000sec / 100mL. In this way, the battery can have good safety performance and rate performance. If the air permeability of the diaphragm is too high, the safety performance of the battery will be reduced and short circuits will occur easily. If the air permeability of the diaphragm is too low, the rate performance of the battery will be reduced.
[0055] In some embodiments, the contact angle of the separator to the electrolyte is ≤60°. In this way, the separator can have good wettability, thereby improving the cycle life of the battery.
[0056] In the present application, the contact angle testing method is: drop an electrolyte (containing 40% ethylene carbonate (EC), 40% dimethyl carbonate (DMC), 1.0 mol / L lithium hexafluorophosphate and 5% vinylene carbonate) directly onto the surface of the diaphragm, take an image of the droplet with an optical contact angle meter, and then use software to automatically measure the contact angle.
[0057] In some embodiments, the breakdown strength of the separator is ≥3.2 N. In this way, the battery can have good safety performance.
[0058] In a second aspect, the present invention also provides a method for preparing a diaphragm, comprising the following steps:
[0059] S1. providing a flame retardant slurry, wherein the flame retardant slurry comprises spirocyclic phosphate bisphenol-S and a first solvent;
[0060] S2, performing film-forming treatment on the surface of the base film with the flame retardant slurry to obtain a wet film layer, and performing a first drying on the wet film layer to obtain a diaphragm;
[0061] Wherein, the structural formula of spirocyclic phosphate bisphenol-S is
[0062] Where n is 500-2500.
[0063] In the present application, the flame retardant slurry is disposed on the surface of the base film, and the flame retardant slurry can be directly coated on the surface of the base film.
[0064] In some embodiments, the flame retardant slurry further comprises a binder, and the preparation process of the flame retardant slurry comprises:
[0065] Spirocyclic phosphate bisphenol-S, a binder and a first solvent are provided, and the spirocyclic phosphate bisphenol-S and the binder are dispersed in the first solvent to obtain a flame retardant slurry.
[0066] In the present application, dispersing the spirocyclic phosphate bisphenol-S and the binder in the first solvent can be achieved by stirring.
[0067] In some embodiments, dispersing spirocyclic phosphate bisphenol-S and a binder in a first solvent comprises:
[0068] Add spirocyclic phosphate bisphenol-S and a binder to the first solvent, stir at room temperature for 2h-8h at a stirring speed of 20RPM-40RPM, evacuate to a vacuum degree of ≤-80 (to remove bubbles generated during stirring), and then stir at a stirring speed of 5RPM-20RPM for 30min-180min. In this way, the uniformity of the flame retardant slurry can be improved and the number of bubbles in the flame retardant slurry can be reduced.
[0069] In some embodiments, the first drying temperature is 85°C-100°C, for example, it can be 85°C, 86°C, 87°C, 88°C, 89°C, 90°C, 91°C, 92°C, 93°C, 94°C, 95°C, 96°C, 97°C, 98°C, 99°C, 100°C, etc., and the first drying time is 20min-180min, for example, it can be 20min, 40min, 60min, 80min, 100min, 120min, 140min, 160min, 180min, etc.
[0070] In some embodiments, the mass ratio of spirocyclic phosphate bisphenol-S, binder and first solvent is (3-10):1:(5-20), for example, it can be 3:1:5, 4:1:7, 5:1:9, 6:1:11, 7:1:13, 8:1:15, 9:1:17, 10:1:20, etc.
[0071] In some embodiments, the preparation method of spirocyclic phosphate bisphenol-S comprises the following steps:
[0072] Providing pentaerythritol, phosphorus oxychloride, a catalyst and a second solvent, mixing the pentaerythritol, phosphorus oxychloride, the catalyst and the second solvent, performing a first heating reaction, cooling and filtering after the reaction, and then performing a second drying on the solid product obtained by filtering to obtain a spirocyclic phosphate dichloride;
[0073] Bisphenol-S, triethylamine and a second solvent are provided, spirocyclic phosphate diacyl chloride, bisphenol-S and the second solvent are mixed, triethylamine is added and a second heating reaction is carried out, the temperature is lowered after the reaction and the product is filtered, and a solid product obtained by the filtration is dried for a third time to obtain spirocyclic phosphate bisphenol-S.
[0074] In the present application, triethylamine can react with HCL produced by the reaction of spirocyclic phosphate diacyl chloride and bisphenol-S, thereby promoting the reaction in the positive direction and improving the yield.
[0075] In some embodiments, the mass ratio of pentaerythritol to phosphorus oxychloride is 1:(1-9), for example, it can be 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, etc. In this way, the yield of the intermediate spirocyclic phosphate dichloride can be improved. The reaction of pentaerythritol and phosphorus oxychloride will produce a large amount of hydrogen chloride gas, which will take away part of the phosphorus oxychloride when it emerges. Excess phosphorus oxychloride can be used to supplement it, so as to promote the reaction to continue; at the same time, the excess phosphorus oxychloride can act as a solvent.
[0076] In some embodiments, the mass ratio of pentaerythritol to phosphorus oxychloride is 1:3.
[0077] In some embodiments, the mass ratio of spirocyclic phosphate diacyl chloride to bisphenol-S is (0.9-1.1):1, for example, 0.9:1, 0.95:1, 1:1, 1.05:1, 1.1:1, etc. In this way, the yield of spirocyclic phosphate bisphenol-S can be improved.
[0078] In some embodiments, the mass ratio of spirocyclic phosphate dichloride to bisphenol-S is 1:1.
[0079] In some embodiments, the reaction temperature of the first heating reaction is 70°C-90°C, for example, it can be 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, etc., and the reaction time of the first heating reaction is 4h-12h, for example, it can be 4h, 5h, 6h, 7h, 8h, 9h, 10h, 11h, 12h, etc.
[0080] In some embodiments, the reaction conditions of the second heating reaction are heating to 70°C-90°C, for example, 70°C, 72°C, 74°C, 76°C, 78°C, 80°C, 82°C, 84°C, 86°C, 88°C, 90°C, etc., and the reaction time of the second heating reaction is 6h-10h, for example, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, etc. In this way, the degree of polymerization of the generated spirocyclic phosphate bisphenol-S can be increased.
[0081] In some embodiments, the second solvent and the third solvent independently include one or more of acetonitrile, propionitrile, butyronitrile, methacrylonitrile, acrylonitrile, dimethylformamide, dimethyl sulfoxide and N-methylpyrrolidone.
[0082] In a third aspect, an embodiment of the present invention provides a battery, comprising the above-mentioned diaphragm or a diaphragm produced by the above-mentioned diaphragm production method.
[0083] The present application is described in detail below by means of specific examples, which are only partial examples of the present application and are not intended to limit the present application. The raw materials used in the following examples are all commercially available products unless otherwise specified.
[0084] Example 1
[0085] A diaphragm and a method for preparing the same, comprising the following steps:
[0086] (1) 400 g of pentaerythritol, 1200 g of phosphorus oxychloride and 100 g of anhydrous aluminum chloride were added to 200 ml of anhydrous acetonitrile, heated to 80° C., and the reaction was stopped after 8 h. The reaction mixture was then naturally cooled to 40° C. while stirring. The reaction solution was poured into cold water for suction filtration and washing. The product was then dried in a thermostat at 80° C. to obtain an intermediate spirocyclic phosphate dichloride;
[0087] (2) 100 g of the intermediate spirocyclic phosphate dichloride and 100 g of bisphenol-S were added to 300 g of acetonitrile, triethylamine was added dropwise at a rate of 4 seconds per drop, and the mixture was heated to 75° C. After reacting for 8 h, the heating was stopped, and the mixture was cooled naturally while stirring. The reaction solution was poured into ice water for suction filtration and washing, and the product was then dried in a thermostat at 80° C. to obtain spirocyclic phosphate bisphenol-S (degree of polymerization n was 500);
[0088] (3) Add 100 g of polyvinylidene fluoride and 500 g of spirocyclic phosphate bisphenol-S to 1000 g of N-methylpyrrolidone, stir at a stirring speed of 30 RPM for 4 h at room temperature, then evacuate to a vacuum degree of -80, reduce the stirring speed to 14 RPM, and stir for 1 h to obtain a flame retardant slurry;
[0089] (4) The flame retardant slurry was evenly coated on both sides of the base film (PE film, thickness 9 μm), and then dried at 90° C. for 100 min to obtain a spirocyclic phosphate bisphenol-S flame retardant composite diaphragm (the thickness of the flame retardant layer was 3 μm).
[0090] Example 2
[0091] This embodiment is basically the same as embodiment 1, except that the amount of phosphorus oxychloride used in step (1) of this embodiment is 2400 g, and the degree of polymerization n of the obtained spirocyclic phosphate bisphenol-S is 1000.
[0092] Example 3
[0093] This embodiment is basically the same as embodiment 1, except that the amount of phosphorus oxychloride used in step (1) of this embodiment is 3600 g, and the degree of polymerization n of the obtained spirocyclic phosphate bisphenol-S is 1000.
[0094] Example 4
[0095] This embodiment is basically the same as embodiment 2, except that in step (2) of this embodiment, the reaction is heated to 80° C., and the degree of polymerization n of the obtained spirocyclic phosphate bisphenol-S is 2100.
[0096] Example 5
[0097] This embodiment is basically the same as embodiment 2, except that in step (2) of this embodiment, the reaction is heated to 85° C., and the degree of polymerization n of the obtained spirocyclic phosphate bisphenol-S is 2100.
[0098] Example 6
[0099] This embodiment is basically the same as embodiment 4, except that the amount of 500 g of spirocyclic phosphate bisphenol-S used in step (3) of this embodiment is 200 g.
[0100] Example 7
[0101] This embodiment is basically the same as embodiment 4, except that the amount of 500 g of spirocyclic phosphate bisphenol-S used in step (3) of this embodiment is 1000 g.
[0102] Example 8
[0103] This embodiment is substantially the same as Embodiment 4, except that the thickness of the flame retardant layer in this embodiment is 1 μm.
[0104] Example 9
[0105] This embodiment is substantially the same as Embodiment 4, except that the thickness of the flame retardant layer in this embodiment is 5 μm.
[0106] Comparative Example 1
[0107] This comparative example is substantially the same as Example 1, except that no flame retardant layer is provided in this comparative example.
[0108] Comparative Example 2
[0109] This comparative example is basically the same as Example 1, except that in step (2) of this comparative example, the reaction is heated to 65° C., the polymerization degree n of the obtained spirocyclic phosphate bisphenol-S is 300, and the thickness of the flame retardant layer is 5 μm.
[0110] Comparative Example 3
[0111] This comparative example is substantially the same as Example 1, except that in this comparative example, the spirocyclic phosphate bisphenol-S is replaced by pentaerythritol melamine phosphate.
[0112] Test Case
[0113] Shrinkage test: The diaphragms obtained in the example and the comparative example were placed in an oven at 160°C and 180°C for 30 min each, and the lengths of the diaphragms before and after the oven treatment were measured to obtain the shrinkage rates of the diaphragms. The test results are shown in Table 1.
[0114] Flammability test: The diaphragms obtained in the examples and comparative examples were ignited with an open flame. If they did not ignite within 10 seconds, they were non-flammable. If they ignited within 10 seconds and had burning marks, they were flammable. The test results are shown in Table 1.
[0115] Table 1
[0116]
[0117] From Table 1, we can see that:
[0118] Compared with Example 4, Example 6 and Example 7, the shrinkage rate of the diaphragm of Example 4 is the smallest at 160° C. and 180° C., which shows that the mass ratio of spirocyclic phosphate bisphenol-S to polyvinylidene fluoride will affect the high-temperature shrinkage rate of the diaphragm.
[0119] Compared with Example 4, Example 8 and Example 9, as the thickness of the flame retardant layer increases, the shrinkage rate of the diaphragm at 160°C and 180°C decreases, and the flammability of the diaphragm decreases. However, the thicker the diaphragm is, the more internal space of the battery it occupies, thereby reducing the energy density of the battery. Therefore, the thickness of the diaphragm should not be too thick.
[0120] Compared with Comparative Example 1, the shrinkage rate of the diaphragm of the embodiment is the smallest at 160° C. and 180° C., which shows that the flame retardant layer in the present application can effectively reduce the high-temperature shrinkage rate of the diaphragm.
[0121] Compared with Comparative Example 2, the membrane of Example 1 has a smaller shrinkage rate at 160°C and 180°C, which shows that the higher the degree of polymerization of the spirocyclic phosphate bisphenol-S, the lower the high-temperature shrinkage rate of the membrane. Compared with Comparative Example 2, the membrane of Example 9 has a smaller shrinkage rate at 160°C and 180°C and is non-flammable, which shows that the higher the degree of polymerization of the spirocyclic phosphate bisphenol-S, the lower the high-temperature shrinkage rate of the membrane and the worse the flammability.
[0122] Compared with Comparative Example 3, the diaphragm of Example 1 has a smaller shrinkage rate at 160°C and 180°C and is non-flammable. It can be seen that the flame retardant effect of spirocyclic phosphate bisphenol-S is better than that of pentaerythritol melamine phosphate, and the shrinkage rate at high temperature is lower.
[0123] Figure 1is the structural formula of spirocyclic phosphate bisphenol-S in this application, Figure 2 This is the infrared spectrum of the spirocyclic phosphate bisphenol-S prepared in Example 1 of the present application. Figure 2 It can be seen that 3000~3100cm -1 It is the stretching vibration of CH in the benzene ring, generally at 1600cm -1 and 1500cm -1 The vibration band of the C=C conjugated system appears at 1600cm, because the benzene ring is adjacent to -O- and -SO2. Due to the resonance of these groups with the benzene nucleus, the -1 The peak of 1480.3cm in the spectrum is further split into two small peaks. -1 and 1454.9cm -1 The absorption peak at 860-800 cm-1 indicates the presence of a benzene ring. -1 , 8413.5cm in the spectrum -1 The absorption peak of the benzene ring can be proved to be a 1,4-substituted structure. The stretching vibration absorption peak position of S=O in R2SO2 is 1350~1300cm -1 , 1300.7cm in the spectrum -1 The absorption peak can prove the existence of -SO2- structure in the final product. 1843.6cm -1 、1149.2cm -1 、1182.9cm -1 The characteristic peak at indicates the POC structure. Therefore, the product is cyclic phosphate bisphenol-S.
[0124] Figure 3 The diaphragms obtained by treating the diaphragms of Example 9 and Comparative Example 1 in an oven at 120°C, 130°C, 160°C, and 180°C for 30 minutes, respectively. Figure 3 It can be seen that the separator of comparative example 1 starts to shrink at 160°C, and the shrinkage rates at 160°C and 180°C are 40.6% and 85% respectively. The separator of example 9 does not shrink at a high temperature of 180°C.
[0125] Figure 4 The diaphragms obtained when the diaphragms of Example 9 and Comparative Example 1 are ignited by open flames. Figure 4 It can be seen that the diaphragm of comparative example 1 starts to burn 3 seconds after ignition, and the flame continues to burn for 10 seconds before extinguishing, and burn marks appear on the diaphragm. Example 9 cannot be ignited.
[0126] In summary, the separator of the present application has excellent thermal stability and flame retardant properties.
[0127] The embodiments of the present invention are described in detail above. Specific examples are used herein to illustrate the principles and implementation methods of the present invention. The description of the above embodiments is only used to help understand the method of the present invention and its core idea. At the same time, for those skilled in the art, according to the idea of the present invention, there will be changes in the specific implementation methods and application scope. In summary, the content of this specification should not be understood as a limitation on the present invention.
Claims
1. A diaphragm, characterized in that: It comprises a base film and a flame retardant layer arranged on the surface of the base film, wherein the material of the flame retardant layer comprises spirocyclic phosphate bisphenol-S, and the structural formula of the spirocyclic phosphate bisphenol-S is Where n is 500-2500.
2. The diaphragm according to claim 1, characterized in that: The thickness of the flame retardant layer is 3 μm to 8 μm; and / or The thickness of the diaphragm is 6 μm to 18 μm; and / or The air permeability of the diaphragm is ≤1000sec / 100mL; and / or The contact angle of the separator to the electrolyte is ≤60°; and / or The breakdown strength of the diaphragm is ≥3.2N.
3. The diaphragm according to claim 1, characterized in that: The material of the base film includes one or more of polyethylene, polypropylene and cellulose.
4. The diaphragm according to claim 1, characterized in that: The material of the flame retardant layer also includes a binder.
5. The diaphragm according to claim 4, characterized in that: The binder comprises one or more of polyvinylidene fluoride and carboxymethyl cellulose; and / or The mass ratio of the spirocyclic phosphate bisphenol-S to the binder is (3-10):
1.
6. A method for preparing a diaphragm, characterized in that: The following steps are involved: Providing a flame retardant slurry, wherein the flame retardant slurry comprises spirocyclic phosphate bisphenol-S and a first solvent; Providing a base film, subjecting the flame retardant slurry to a film-forming treatment on the surface of the base film to obtain a wet film layer, and performing a first drying on the wet film layer to obtain a diaphragm; Wherein, the structural formula of the spirocyclic phosphate bisphenol-S is Where n is 500-2500.
7. The method for preparing a diaphragm according to claim 6, characterized in that: The flame retardant slurry further comprises a binder, and the preparation process of the flame retardant slurry comprises: Provide spirocyclic phosphate bisphenol-S, a binder and a first solvent, and disperse the spirocyclic phosphate bisphenol-S and the binder in the first solvent to obtain a flame retardant slurry.
8. The method for preparing a diaphragm according to claim 7, characterized in that: The mass ratio of the spirocyclic phosphate bisphenol-S, the binder and the first solvent is (3-10):1:(5-20).
9. The method for preparing a diaphragm according to claim 6, characterized in that: The first drying temperature is 85° C.-100° C., and the first drying time is 20 min-180 min.
10. The method for preparing a diaphragm according to claim 6, characterized in that: The preparation method of the spirocyclic phosphate bisphenol-S comprises the following steps: Providing pentaerythritol, phosphorus oxychloride, a catalyst and a second solvent, mixing the pentaerythritol, the phosphorus oxychloride, the catalyst and the second solvent, performing a first heating reaction, cooling and filtering after the reaction, and then performing a second drying on the solid product obtained by filtering to obtain a spirocyclic phosphate dichloride; Bisphenol-S, triethylamine and a second solvent are provided, the spirocyclic phosphate dichloride, the bisphenol-S and the second solvent are mixed, triethylamine is added and a second heating reaction is performed, the temperature is lowered after the reaction and the product is filtered, and a solid product obtained by filtration is dried for a third time to obtain spirocyclic phosphate bisphenol-S.
11. The method for preparing a diaphragm according to claim 10, characterized in that: The mass ratio of the pentaerythritol to the phosphorus oxychloride is 1:(1-9); and / or The mass ratio of the spirocyclic phosphate dichloride to the bisphenol-S is (0.9-1.1):1; and / or The reaction temperature of the first heating reaction is 70° C.-90° C., and the reaction time of the first heating reaction is 4 h-12 h; and / or The reaction condition of the second heating reaction is heating to 70° C.-90° C., and the reaction time of the second heating reaction is 6 h-10 h.
12. A battery, characterized in that: A diaphragm comprising the diaphragm according to any one of claims 1 to 5 or a diaphragm prepared by the method for preparing the diaphragm according to any one of claims 6 to 11.
Citation Information
Patent Citations
Diaphragm as well as preparation method and application thereof
CN112864533A
Flame-retardant composite battery diaphragm as well as preparation method and application thereof
CN114284636A
Range filter type household exhaust system
KR102352051B1